Inflammatory markers including NLR, AFR and SII as prognostic factors in neuroblastoma - Chenglong Zhang; Xiaoyu Wang; Yu Tian; Huizhong Niu; Pengju Zhang; Jianlei Geng (Scientific Reports)
Abstract Neuroblastoma (NB) is a common pediatric solid tumor, particularly in children under 2 years. While survival rates for low- and intermediate-risk NB have improved, the prognosis for high-risk patients remains poor. Inflammation plays a crucial role in tumor progression, and systemic inflammation markers have prognostic value in various cancers. This study investigates the prognostic significance of neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII), and albumin-to-fibrinogen ratio (AFR) in NB patients. A retrospective analysis was conducted on 166 NB patients diagnosed between January 2013 and November 2024 at Hebei Provincial Children’s Hospital. Preoperative blood parameters, including neutrophil, lymphocyte, platelet counts, albumin, and fibrinogen levels, were used to calculate NLR, SII, and AFR. ROC curves assessed the relationship between these markers and patient outcomes. Kaplan-Meier survival analysis and Cox regression were performed to evaluate their prognostic value. NLR and SII had high predictive value for mortality, with ROC AUCs of 0.90 and 0.89, respectively. AFR had lower predictive value (AUCs of 0.73 and 0.74). Kaplan-Meier analysis showed that high NLR, low AFR, and high SII correlated with poorer overall survival (OS) and event-free survival (EFS). Both univariate and multivariate Cox regression identified NLR and SII as independent risk factors for OS and EFS. This study demonstrates the prognostic value of NLR, SII, and AFR in the evaluation of NB prognosis, particularly highlighting the efficacy of NLR and SII in predicting mortality and recurrence risks.